Interventions for preventing or treating malnutrition in problem drinkers who are homeless or vulnerably housed: protocol for a systematic review. Issue 1 (December 2015) - Thorley, Helen; Porter, Katie; Fleming, Clare; Jones, Tim; Kesten, Joanna; Marques, Elsa; Richards, Alison; Savović, Jelena
Abstract Background Problem alcohol drinking in homeless and vulnerably housed people can lead to malnutrition, which is associated with complications such as alcohol-related brain damage. Homeless alcohol drinkers are likely to have worse health outcomes and different nutritional needs compared with housed alcohol-drinking persons. It is not clear whether interventions to improve nutritional status in this population have been effective. The purpose of this review is to assess the effectiveness and cost-effectiveness of interventions for preventing or correcting micronutrient deficiencies and other forms of malnutrition and related comorbidities in this population. Methods/design A systematic search for studies of a nutrition-based intervention applied in the homeless or vulnerably housed population with problem drinking will be conducted. The following electronic databases will be systematically searched for relevant studies: MEDLINE, EMBASE, Web of Science, PsycINFO, CAB abstracts, CINAHL, Cochrane Public Health Group Register and Cochrane Drugs and Alcohol Group Register. Screening of identified abstracts for relevance and assessment of papers for inclusion will be done in duplicate. One reviewer will extract data from the studies and assess quality, and this will be checked by another reviewer. Discrepancies will be resolved by consensus. The primary outcomes are (mal)nutrition status or micronutrient deficiencies or change in (mal)nutrition status or micronutrient deficiencies, measures of liver damage and cognitive function. Secondary outcomes include comorbidities, quality of life and functional scales, resources used to deliver treatment, uptake/acceptability of the intervention and engagement with treatment services. Results will be analysed descriptively, and, if appropriate, meta-analyses will be performed. Discussion The results of this review should help to inform the development of effective interventions that can be implemented in the community to improve the health of homeless people who are problem drinkers. Systematic review registration PROSPEROCRD42015024247